Energy efficient sensor data logging with amnesic flash storage - Nath, Suman (2009 International Conference on Information Processing in Sensor Networks, 2009)
We present FlashLogger, an energy-efficient sensor data logging system that uses lazy amnesic compression in a flash-efficient manner. FlashLogger incorporates a suite of compression algorithms suitable for progressively compressing time series scalar, audio, and image data. It uses a novel data structure for efficiently organizing and querying compressed data on flash memory. All our methods are designed for the limited memory and processing capabilities typical of low power sensor nodes, and are prototyped on Tmote Sky platform running TinyOS. Evaluation of FlashLogger with several real world data sets shows orders of magnitude energy savings for both logging data and retrieving data within a time range.